Optimization of Financial Penalties for Environmental Pollution by Chinese Traditional Energy Enterprises - Chang, Le; Song, Yadong; Yu, Tao (Frontiers in Environmental Science, 2020)
The formulation of proper financial penalties plays an important role in regulating Chinese traditional energy enterprises’ illegal pollution. Through the construction of a mixed-strategy game model and an evolutionary game model for regulatory agencies and traditional energy enterprises, the article studies how financial penalties impact players’ strategies and evolutionary processes to optimize financial penalties. It found that excessive financial penalties could reduce enforcement, but insufficient financial penalties would cause more pollution discharge violations. The article concludes that Chinese environmental laws should focus more on setting reasonable penalties based on the profit from activities that generate illegal pollution rather than on the environmental damage to improve regulatory effectiveness.